GAMBARAN PENGETAHUAN IBU DALAM MENINGKATKAN KESEHATAN GIGI DAN MULUT ANAK DI RT 01 DESA PURWASARI (Politeknik Kesehatan Kemenkes Bandung, 2021)
Dental health is important, especially for elementary school age children. The knowledge of parents, especially mothers, in improving dental and oral health has a significant influence on dental and oral health in children, because mothers are the closest people to children. The purpose of this research is to know the description of mother's knowledge in improving the dental and oral health of children in RT 01 Purwasari Village. This research method is descriptive research. The population of this study were 126 mothers who had children of primary school age, namely 6 to 12 years. Sampling by purposive sampling and presented in the form of a frequency distribution table. The results showed that knowledge about how to brush teeth was 57.1% had good criteria, 32.1% had moderate criteria, and 10.7 was lacking. Knowledge about the time of brushing teeth there are 69.6% have good criteria and 30.4% have moderate criteria. And knowledge about healthy food for teeth there are 69.6% have good criteria, 26.8% have moderate criteria, and 3.6% have poor criteria. Mother's knowledge of dental and oral health needs to be maintained and increased through outreach activities from community health centers.